2013
DOI: 10.1371/journal.pone.0074229
|View full text |Cite
|
Sign up to set email alerts
|

Stress Responsive Proteins Are Actively Regulated during Rice (Oryza sativa) Embryogenesis as Indicated by Quantitative Proteomics Analysis

Abstract: Embryogenesis is the initial step in a plant’s life, and the molecular changes that occur during embryonic development are largely unknown. To explore the relevant molecular events, we used the isobaric tags for relative and absolute quantification (iTRAQ) coupled with the shotgun proteomics technique (iTRAQ/Shotgun) to study the proteomic changes of rice embryos during embryogenesis. For the first time, a total of 2 165 unique proteins were identified in rice embryos, and the abundances of 867 proteins were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…These cellular responses, helping in the prevention or alleviation of cellular damage, the re-establishment of homeostatic conditions and the resumption of growth, often mimics certain normal stages of development2930. Thus, there is a broader overlapping set of genes and their cognate proteins involved in developmental processes and stress responses which are driven by systematic regulation of gene expression31323334. Our data showed that gene OsSGL participated in the regulation of both stress-tolerance and yield component traits in rice.…”
Section: Discussionmentioning
confidence: 64%
“…These cellular responses, helping in the prevention or alleviation of cellular damage, the re-establishment of homeostatic conditions and the resumption of growth, often mimics certain normal stages of development2930. Thus, there is a broader overlapping set of genes and their cognate proteins involved in developmental processes and stress responses which are driven by systematic regulation of gene expression31323334. Our data showed that gene OsSGL participated in the regulation of both stress-tolerance and yield component traits in rice.…”
Section: Discussionmentioning
confidence: 64%
“…The proteins were isolated using trichloroacetic acid (TCA) [ 23 ]. About 20 mg of pooled protein from control or salt stress treated samples was labeled with iTRAQ reagents according to the manufacturer’s instructions (iTRAQ Reagents Multiplex kit, Applied Biosystems/MDS Sciex, Foster City, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, an alternative approach has been developed using isobaric tag for relative and absolute quantitation (iTRAQ) as a mass spectrometry-based quantitative technology; this technique overcomes some of the limitations of 2-DE, especially for multiple samples, and allows identification of a greater number of proteins to provide more reliable quantitative information [28, 29]. The advantages of iTRAQ technology have been exploited to identify and quantify 2165 proteins in developing rice embryos [30] and 1815 proteins in wheat grains [31]. …”
Section: Introductionmentioning
confidence: 99%